Taxonomic notes on three species of Epimedium (Berberidaceae) endemic to China - Zhang, Yanjun; Dang, Haishan; Li, Jianqiang; Wang, Ying (Phytotaxa, 2015)
Three species of Epimedium (Berberidaceae), E. reticulatum, E. shuichengense and E. truncatum, are controversial based on flower characteristics. In this paper, the descriptions of their flower characters of these three species are revised based on our extensive studies in herbaria and observations in the field and cultivation. E. reticulatum is transferred from ser. Brachycerae to ser. Campanulatae, and E. shuichengense is recognized as a member of ser. Davidianae. The holotype and isotypes of E. reticulatum represent two species, E. reticulatum and E. membranaceum, and the type material of E. truncatum has been lost. Here we lectotypy E. reticulatum and neotypify E. truncatum.